Lessons learned from investigating EFL pre-service teachers competencies - Didi Sukyadi; Ika Lestari Lestari Damayanti; Fuad Abdul Hamied; Wawan Gunawan; Kurniawan Suryatama; Firly Asyifa (Studies in English Language and Education, 2025)
This study investigates the English proficiency levels, perceptions, and pedagogical competencies of pre-service English teachers who graduated from one of the teacher education universities in Indonesia, along with stakeholder evaluations and future quality benchmarks. This research employed a mixed-methods case study approach, with data collected from TOEFL-like test score reports and a survey involving 52 pre-service teachers, two classroom observations, interviews with two employers, and focus group discussions (FGD) involving four stakeholders from other teacher education universities. Score report and survey data were analyzed through descriptive statistics, while observation notes, employers interviews, and FGD data were analyzed using thematic analysis. The findings from the report revealed that most pre-service teachers possessed B2 or higher English proficiency. The survey result showed that they valued courses on English for Young Learners and general pedagogy clusters, though several courses on the English for Specific Purposes cluster were perceived as less supportive. Classroom observations and employer feedback revealed strong pedagogical competencies, creative use of resources, and technology integration abilities, while also indicating the need for future improvement. Additionally, FGD results emphasized the need for pre-service teachers to master TPACK, obtain standardized English certification, develop leadership skills, possess AI ethico-onto-epistemological awareness, and demonstrate competence in multiliteracies and multimodal pedagogies.